2018
DOI: 10.3233/wor-182819
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with neck disorders among university student smartphone users

Abstract: BACKGROUND: In our digital society, the use of smartphones has increased rapidly. Parallel with the growing use of smartphones, musculoskeletal problems associated with intensive smartphone use have also increased. Neck flexion is the most commonly adopted posture by smartphone users while looking at the visual display terminals of smartphones for extended periods; this posture may lead to neck disorders. OBJECTIVE: The purpose of the current study was to investigate musculoskeletal disorders (MSDs) in smartph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
2
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 26 publications
9
59
2
10
Order By: Relevance
“…Other studies in students and workforces also reported results similar to the present study [55][56][57]. In contrast to these results, a recent study showed that an increase in age increases the possibility of developing musculoskeletal disorders in the students' neck [58]. In general, increase in age has always been recognized as a significant risk factor for musculoskeletal disorders in previous studies [59].…”
Section: Discussionsupporting
confidence: 81%
“…Other studies in students and workforces also reported results similar to the present study [55][56][57]. In contrast to these results, a recent study showed that an increase in age increases the possibility of developing musculoskeletal disorders in the students' neck [58]. In general, increase in age has always been recognized as a significant risk factor for musculoskeletal disorders in previous studies [59].…”
Section: Discussionsupporting
confidence: 81%
“…This has implications for the vertical location of digital displays: if a computer display is located above eye height then a worker is more likely to tip their head backwards to view the display [6,7], increasing their neck flexion, which in turn can contribute to physical discomfort. The literature reports that visual and physical comfort can be improved if visual displays are below eye height [6,7] but they should not be located so low that it induces increased neck flexion and head tilt to view the display [11,12].…”
Section: Viewing Heightmentioning
confidence: 99%
“…This then poses a dilemma for the user. If they choose to maintain a comfortable arm posture, then they will need to flex their head and neck forward to view the display, as has been shown to occur with laptop computers [11], tablets [13] and smartphones [12,14] (see Fig. 1).…”
Section: Viewing Heightmentioning
confidence: 99%
“…The involved investigations were from altered countries with varied answer rates from 62.2% to 100% (Table 1). Students were the main participants in these (Chiang and Liu, 2016;Gustafsson et al, 2018;Im, Cho, Park, Jung and Park, 2010;Kietrys, Gerg, Dropkin and Gold, 2015;Kim and Kim, 2015;Namwongsa, Puntumetakul, Neubert and Boucaut, 2018;Szucs et al, 2018;Woo et al, 2016;Xiong and Muraki, 2014;Jin, Kim, Park, Chang and Kim et al, 2019). On other hand, some scholars in other studies also employed working participants (Lee, Hsu, Bair, Toberman and Chien, 2018;So, Cheng and Szeto, 2017;Wilaiwan and Siriwong, 2019).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Types of mobile devices used in the designated studies encompassed tablets (Chiang and Liu, 2016;Lee et al, 2018;Razvi et al, 2018;Szucs et al, 2018), handheld electronic game devices (Razvi et al, 2018;Woo et al, 2016;Wilaiwan and Siriwong, 2019) and mobile phones which consisted of cell phones, keypad phones, smartphones and touchscreen phones (D'Anna et al, 2018;Gustafsson et al, 2018;Gustafsson et al, 2017;Im, Cho, Park, Jung and Park, 2010;Kietrys et al, 2015;Kim and Kim, 2015;Korpinen, Paakkonen and Gobba, 2013;Namwongsa et al, 2018;Razvi et al, 2018;So et al, 2017;Szucs et al, 2018;Werth and Babski-Reeves, 2014;Woo et al, 2016;Xie, Szeto and Dai, 2017;Xiong andMuraki, 2014, Wilaiwan andSiriwong, 2019;Jin, Kim, Park, Chang and Kim et al,2019). Day-to-day duration of the use of the smartphone devices fluctuated between 1 hour to 6 hours among users (D'Anna et al, 2018;Kim and Kim, 2015;Namwongsa et al, 2018;Razvi et al, 2018;So et al, 2017;Woo et al, 2016;Wilaiwan and Siriwong, 2019). Participants used their handheld devices frequently for the following activities; making phone calls, texting messages, internet browsing and playing games, as informed by the encompassed studies (Chiang and Liu, 2016;D'Anna et al, 2018;Gustafsson et al, 2018;…”
Section: Study Characteristicsmentioning
confidence: 99%